2018
DOI: 10.3390/catal8010010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Substrate Promiscuity and Chiral Selectivity of Esterases from Phylogenetically and Environmentally Diverse Microorganisms

Abstract: Substrate specificity and selectivity of a biocatalyst are determined by the protein sequence and structure of its active site. Finding versatile biocatalysts acting against multiple substrates while at the same time being chiral selective is of interest for the pharmaceutical and chemical industry. However, the relationships between these two properties in natural microbial enzymes remain underexplored. Here, we performed an experimental analysis of substrate promiscuity and chiral selectivity in a set of 145… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Individual enzyme enantiomeric excess data evaluated by GC chromatography is included in our master data Tables S2.1 and S2.2. A previous study that included a panel of 145 wild-type microbial esterases unambiguously concluded that there is a direct relationship between enzyme enantioselectivity and substrate specificity . In addition, ancestral enzymes are generally considered to have a broader substrate scope compared to enzymes sourced from extant genes .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual enzyme enantiomeric excess data evaluated by GC chromatography is included in our master data Tables S2.1 and S2.2. A previous study that included a panel of 145 wild-type microbial esterases unambiguously concluded that there is a direct relationship between enzyme enantioselectivity and substrate specificity . In addition, ancestral enzymes are generally considered to have a broader substrate scope compared to enzymes sourced from extant genes .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A previous study that included a panel of 145 wild-type microbial esterases unambiguously concluded that there is a direct relationship between enzyme enantioselectivity and substrate specificity. 35 In addition, ancestral enzymes are generally considered to have a broader substrate scope compared to enzymes sourced from extant genes. 36 The enantioselectivity results of our 101enzyme panel when tested with substrate 1a support this general scientific consensus.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, in the present issue, Coscolín and coworkers [36] and Nguyen and coworkers [37] investigated the properties and catalytic performance of biocatalysts newly isolated from genomes and metagenomes. In particular, Coscolín and coworkers investigated an ample set of metagenomicsderived esterases and lipases to reveal the extent by which promiscuity and selectivity co-exist in these catalytically-important biocatalysts, so as to identify chiral selective and promiscuous esterases and lipases.…”
Section: The Present Issuementioning
confidence: 99%
“…A recent report from Pfizer comparing 57 wild-type ERED enzymes and 56 ASR-derived EREDs demonstrated that ASR enzymes were significantly less enantioselective than their wild-type counterparts. 44 Decreased enantioselectivity has been reported to correlate with increased substrate promiscuity, 45 which may indicate that ASR enzymes have broader substrate scopes than wild-type enzymes, but that they are more likely to display lower enantioselectivity.…”
Section: Acs Catalysismentioning
confidence: 99%